Yeah men an audience study on Magic 89.9's Boys Night Out and the male identity - Reyes, Jonas Ethan Dela Rosa 1993-; Avecilla, Victor C.; University of the Philippines. College of Mass Communication (2014)
"This study is an audience study on Magic 89.9's Boys Night Out in relation to how a male listener identifies with the male identity embodied in the program. Boys Night Out is an evening radio talk show in Magic 89.9, an FM radio station, which airs regularly from Monday to Thursday from 6pm to 10 pm and talks about casual topics such as love, lust and malice in a comedic and light manner and coming from a male perspective. It aims to find out how a male listener identifies with the male identity that is embodies by Boys Night Out and its hosts. The theory of identification with media characters was utilized in this study. Male audiences of Boys Night Out are constantly exposed to the ideologies and views of the world that program and its hosts embody in every episode and these shape their individual identities as men and their understanding of their role as a male member of the society they belong to. Interviews are used by the researcher as an audience research method. In the case of this study, the researcher conducts in-depth questionings with nine respondents. The respondents of the study are frequent and long term male listener of Boys Night Out. Each respondent will be subject to 14 questions."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Radio audiences -- Philippines -- Attitudes; Radio talk shows -- Philippines; Men--Identity.